1999
DOI: 10.1152/jn.1999.82.6.3236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Saccades Perturbed by Stimulation of the Rostral Superior Colliculus, the Caudal Superior Colliculus, and the Omnipause Neuron Region

Abstract: Over the past decade, considerable research efforts have been focused on the role of the rostral superior colliculus (SC) in control of saccades. The most recent theory separates the deeper intermediate layers of the SC into two functional regions: the rostral pole of these layers constitutes a fixation zone and the caudal region comprises the saccade zone. Sustained activity of fixation neurons in the fixation zone is argued to maintain fixation and help prevent saccade generation by exciting the omnipause ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 71 publications
9
64
0
Order By: Relevance
“…Below, we discuss how these findings lead to reconsider the functional scheme that is commonly proposed to explain how the brain generates saccades toward a moving target (Optican, 2009). Previous studies have tested the robustness of gaze saccades toward a static target and shown that the orienting system compensates for changes in gaze position induced by a brief electrical stimulation within oculomotor regions like the dSC (Schiller and Sandell, 1983;Sparks and Mays, 1983;Pélisson et al, 1989Pélisson et al, , 1995Gandhi and Keller, 1999), the paramedian pontine reticular formation (Sparks et al, 1987), or the nucleus raphe interpositus (Paré and Guitton, 1998;Gandhi and Keller, 1999;Gandhi and Sparks, 2007). The numerous examples of unchanged accuracy between unperturbed and perturbed saccades reported in our study (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…Below, we discuss how these findings lead to reconsider the functional scheme that is commonly proposed to explain how the brain generates saccades toward a moving target (Optican, 2009). Previous studies have tested the robustness of gaze saccades toward a static target and shown that the orienting system compensates for changes in gaze position induced by a brief electrical stimulation within oculomotor regions like the dSC (Schiller and Sandell, 1983;Sparks and Mays, 1983;Pélisson et al, 1989Pélisson et al, , 1995Gandhi and Keller, 1999), the paramedian pontine reticular formation (Sparks et al, 1987), or the nucleus raphe interpositus (Paré and Guitton, 1998;Gandhi and Keller, 1999;Gandhi and Sparks, 2007). The numerous examples of unchanged accuracy between unperturbed and perturbed saccades reported in our study (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…An important feature of the superior colliculus is its subdivision in two functionally distinct regions. The rostral colliculus contains neurons that discharge when a stimulus in the central $2 of the visual field is actively fixated (Munoz and Wurtz, 1992;1993b;Gandhi and Keller, 1999), while neurons in the caudal colliculus show activity related to the preparation and execution of saccades (Dorris et al, 1997). In patients with neglect following a right cortical lesion, a functionally disinhibited left colliculus would exhibit increased fixational activity in its rostral region and increased saccade-related activity in its caudal region.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a distracter presented simultaneously with the target, but in the opposite hemifield, systematically increases saccade latency, which has been termed the remote distracter effect (Walker et al, 1995(Walker et al, , 1997. Both effects are specific to eye movements and have been attributed to inhibitory interactions within the oculomotor system, in particular the superior colliculus Wurtz, 1992, 1993b;Walker et al, 1997;Gandhi and Keller, 1999). Interestingly, a classic hypothesis has related the lateral orienting bias that characterizes spatial neglect to a loss of balance between the neocortex and the superior colliculus (Sprague, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…SN pause firing during fixations while producing bursts of spikes prior to and during saccades directed to their response field (Sparks et al 1976;Wurtz and Goldberg 1972;Munoz and Wurtz 1995a). Converging data from microstimulation studies (Gandhi and Keller 1999;Robinson 1972) and single cell recordings (Krauzlis et al 1997;Wurtz 1993a, 1995b) reveal that FN like SN still possess a movement field, i.e., activity of FN is associated with small contraversive saccades. 3 It is not known whether microsaccades that occur involuntarily during fixation originate in the rostral pole of the SC as proposed by Gandhi and Keller (1999) and Munoz et al (2000).…”
Section: Prolongation Of Saccade Latencies Following Microsaccadesmentioning
confidence: 99%
“…Converging data from microstimulation studies (Gandhi and Keller 1999;Robinson 1972) and single cell recordings (Krauzlis et al 1997;Wurtz 1993a, 1995b) reveal that FN like SN still possess a movement field, i.e., activity of FN is associated with small contraversive saccades. 3 It is not known whether microsaccades that occur involuntarily during fixation originate in the rostral pole of the SC as proposed by Gandhi and Keller (1999) and Munoz et al (2000). Our findings that there is a drop of microsaccade rate prior to saccades and an increase of SRTs in both memory and visual trials when microsaccades occurred around the time of the go signal are consistent with this explanation.…”
Section: Prolongation Of Saccade Latencies Following Microsaccadesmentioning
confidence: 99%